2015
DOI: 10.12816/0009790
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative versus Postoperative Intra-Incisional Bupivacaine - Lidocaine Mixture Infiltration on Early Postoperative Pain after Laparoscopic Cholecystectomy

Abstract: Objective: To compare the postoperative pain relief quality of intra-incisional local infiltration of lidocaine-bupivacaine mixture, pre-or post-laparoscopic cholecystectomy. Methods: Our prospective and randomized investigation included 110 adult patients, of both genders, middle aged, classed I-II by the American society of anesthesiologists and scheduled for elective laparoscopic cholecystectomy after written informed consent and local ethics committee approval had been obtained at Prince Ali Bin Hussein Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Omar Abuelaish and colleagues from Jordan also reported similar findings. 7 However, Saurabh Agrawal 18 concluded that intraperitoneal instillation of bupivacaine does not reduce postoperative pain significantly. Marcelo S also described similar observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omar Abuelaish and colleagues from Jordan also reported similar findings. 7 However, Saurabh Agrawal 18 concluded that intraperitoneal instillation of bupivacaine does not reduce postoperative pain significantly. Marcelo S also described similar observations.…”
Section: Discussionmentioning
confidence: 99%
“…It avoids complications associated with opioids such as postoperative nausea vomiting and respiratory depression. 7 Patient has smooth recovery and early discharge from hospital. Bupivacaine is an amide local anaesthetic.…”
Section: Introductionmentioning
confidence: 99%